Oxygen‐Sensing Chemiluminescent Iridium(III) 1, 2‐Dioxetanes: Unusual Coordination and Activity. Issue 1 (22nd November 2022) - Kagalwala, Husain N.; Bueno, Lorena; Wanniarachchi, Hashini; Unruh, Daniel K.; Hamal, Khagendra B.; Pavlich, Cyprian I.; Carlson, Graham J.; Pinney, Kevin G.; Mason, Ralph P.; Lippert, Alexander R.
Abstract: Next generation chemiluminescent iridium 1, 2‐dioxetane complexes have been developed which consist of the Schaap's 1, 2‐dioxetane scaffold directly attached to the metal center. This was achieved by synthetically modifying the scaffold precursor with a phenylpyridine moiety, which can act as a ligand. Reaction of this scaffold ligand with the iridium dimer [Ir(BTP)2 (μ‐Cl)]2 (BTP=2‐(benzo[ b ]thiophen‐2‐yl)pyridine) yielded isomers which depict ligation through either the cyclometalating carbon or, interestingly, the sulfur atom of one BTP ligand. Their corresponding 1, 2‐dioxetanes display chemiluminescent responses in buffered solutions, exhibiting a single, red‐shifted peak at 600 nm. This triplet emission was effectively quenched by oxygen, yielding in vitro Stern‐Volmer constants of 0.1 and 0.009 mbar −1 for the carbon‐bound and sulfur compound, respectively. Lastly, the sulfur‐bound dioxetane was further utilized for oxygen sensing in muscle tissue of living mice and xenograft models of tumor hypoxia, depicting the ability of the probe chemiluminescence to penetrate biological tissue (total flux ∼10 6  p/s). Abstract : New chemiluminescent iridium (III) complexes with directly attached Schaap 1, 2‐dioxetane scaffolds are reported. Two isomers, IrCL‐4 and IrCL‐5 have been isolated and investigated, with the latter displaying an unusual sulfur ligation. Both demonstrate oxygen‐dependent chemiluminescent responses in vitro, with the ionic IrCL‐5 being employed for oxygen sensing in live mice.